Development of Educational Material for Teaching Composition in Light of The Contextual Approach - Setiawan, Wahid Budi; Sutaman, Sutaman; Al Anshory, Abdul Muntaqim (JURNAL IJ-ATL, 2022)
This research started from the need of the Muhammadiyah Al-Munawarah Institute for teaching some Arabic language lessons, including teaching composition. Teaching composition in it used various materials so that the educational production did not achieve the desired educational goal. This research aims to: 1) Reveal the process of developing the educational material for teaching composition in light of the contextual approach at the Muhammadiyah Al-Munawarah Institute in Malang. 2) Know the validity of the educational material for teaching composition developed in light of the contextual approach at the Muhammadiyah Al-Munawarah Institute in Malang. 3) Measure the effectiveness of using the educational material for teaching composition developed in light of the contextual approach at the Muhammadiyah Al-Munawarah Institute in Malang. This research is a qualitative and quantitative research using the research and development method. The results of the research are: 1) The educational material was developed in light of the contextual approach that benefits from the development steps of Borg and Gall, which consist of needs and problems analysis, data collection, production design, production validation, first production experiment, production modification, second production experiment, second/final modification. The developed product is in the form of a book, consisting of the introductory pages (cover, introduction, material content, material usage guide), the main pages (vocabulary, text and exercises), and the last page (author's biography), 2) The validity of the developed product according to experts is very good, 3) The developed composition teaching material is effective for students at the Institute of Muhadiyat al-Munawarah Malang, as the value of t-calculation = 9.2 and was greater than the theoretical t-value of 2.145.